2011
DOI: 10.1029/2011jg001647
|View full text |Cite
|
Sign up to set email alerts
|

Fossil organic matter characteristics in permafrost deposits of the northeast Siberian Arctic

Abstract: [1] Permafrost deposits constitute a large organic carbon pool highly vulnerable to degradation and potential carbon release due to global warming. Permafrost sections along coastal and river bank exposures in NE Siberia were studied for organic matter (OM) characteristics and ice content. OM stored in Quaternary permafrost grew, accumulated, froze, partly decomposed, and refroze under different periglacial environments, reflected in specific biogeochemical and cryolithological features. OM in permafrost is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
213
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 195 publications
(226 citation statements)
references
References 58 publications
12
213
1
Order By: Relevance
“…Especially the interstadial deposits of MIS 3 (core sections 3-1 and 3-2) show the highest accumulation of OM as characteristic for Yedoma deposits (Schirrmeister et al, 5 2013). The measured TOC/TN values of 5 to 12 are within the range of terrestrial permafrost deposits reported for the NE Siberian Arctic (Wetterich et al, 2009;Schirrmeister et al, 2011a;Strauss et al, 2015). Usually, the TOC/TN ratio describes the amount of sedimentary OM that originates from aquatic vs. terrestrial sources and is commonly used to characterize the dominant origin of the OM (Meyers and Teranes, 2002).…”
Section: Organic Matter Characterizationmentioning
confidence: 81%
See 2 more Smart Citations
“…Especially the interstadial deposits of MIS 3 (core sections 3-1 and 3-2) show the highest accumulation of OM as characteristic for Yedoma deposits (Schirrmeister et al, 5 2013). The measured TOC/TN values of 5 to 12 are within the range of terrestrial permafrost deposits reported for the NE Siberian Arctic (Wetterich et al, 2009;Schirrmeister et al, 2011a;Strauss et al, 2015). Usually, the TOC/TN ratio describes the amount of sedimentary OM that originates from aquatic vs. terrestrial sources and is commonly used to characterize the dominant origin of the OM (Meyers and Teranes, 2002).…”
Section: Organic Matter Characterizationmentioning
confidence: 81%
“…The LP glacial period have slowed down decomposition of soil OM and led to the accumulation of higher amounts of organic carbon under anaerobic conditions with higher aliphatic character to the soils Schirrmeister et al, 2011a;Wetterich et al, 2014). The Yedoma samples (comprising MIS 3 and partly MIS 4) with a higher proportion of the aliphatic component n-nonen (Fig.…”
Section: Organic Matter Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…3). The IC is characterized by the occurrence of syngenetic ice wedges embedded in ice-rich silts and sands, peat horizons and a considerable overall amount of organic carbon (total organic carbon content of up to 5 % by weight; Schirrmeister et al, 2011a). The oldest IC deposits lie up to 10 m below modern sea level at Muostakh Island and are underlain by silts, sands and gravels interpreted as fluvial deposits of Pliocene to Early Pleistocene age ( Fig.…”
Section: Permafrost Propertiesmentioning
confidence: 99%
“…The permafrost of Muostakh Island belongs to Late Pleistocene Yedoma IC deposits that accumulated in the region between at least 46.8 and 19.5 ka BP based on radiocarbon ages (Schirrmeister et al, 2011a). It is overlain by a Holocene peat cover (Fig.…”
Section: Permafrost Propertiesmentioning
confidence: 99%